Methane dry reforming with CO2 over ceria supported Ni catalyst prepared by reverse microemulsion synthesis. (1st June 2022) - Rashid, Muhammad Usman; Wan Daud, Wan Mohd Ashri; Mohidem, Nur Atikah; Mohamad, Mardawani Binti; Akhtar, Javaid; Azam, Mudassar; Miran, Waheed
Highlights: Oxygen mobility exhibited a major role in the decrease of carbon deposition. 40% Ni/CeO2 catalyst prepared by microemulsion showed higher catalytic activity. 20% Ni/CeO2 catalyst exhibited shell-like carbon deposits. Whisker-like carbon species were exhibited by 40% Ni/CeO2 and 80% Ni/CeO2 . Abstract: Reverse microemulsion synthesis route was employed for the preparation of Ni/CeO2 catalysts with the aim of their application in dry reforming of methane. The catalytic activity and stability of the prepared catalysts was investigated in the temperature range of 550–800 °C with the ratio of CH4 /CO2  = 1 and at high gas hourly space velocity (GHSV) of reactants (1.2 × 10 5 ml h −1 g −1 ). In the prepared series of catalysts (20% Ni/CeO2, 40% Ni/CeO2, 80%Ni/CeO2 ); 40% Ni/CeO2 (NC2) exhibited higher catalytic activity and better stability compared to 20% Ni/CeO2 (NC1) and 80% Ni/CeO2 (NC3). Moreover, results indicated that NC2 was found to be stable catalyst for both gas yield and H2 /CO ratio. This study indicated that proper balance between Ni metal and CeO2 content played a critical role in the achievement of better catalyst performance and in the decrease of carbon deposition. The characterization of fresh and spent catalysts was done by BET, XRD, TPR-H2, EDX and TEM.